Ghost Ileostomy Release Down-Our Initial Experience - Khan, Mudassir Ahmad; Baba, Arshad; Wani, Rouf Ahmad; Mehraj, Asif; Parray, Fazl Q; Chowdri, Nisar Ahmad (Journal of Coloproctology, 2023)
Background Many publications describe the advantages of the creation of ghost ileostomy (GI) to prevent the need for formal covering ileostomy in more than 80% of carcinoma rectum patients. However, none of the papers describes exactly how to ultimately remove the GI in these 80% of patients in whom it doesn't need formal maturation.Aim To describe and evaluate the ghost ileostomy release down (GIRD) technique in terms of feasibility, complications, hospital stay, procedure time etc. in patients with low anterior resection/ultra-low anterior resection (LAR/uLAR) with GI for carcinoma rectum.Method The present was a prospective cohort study of patients with restorative colorectal resections with GI for carcinoma rectum, Postoperatively the patients were studied with respect to ease and feasibility of the release down of GI and its complications. The data was collected, analyzed and inference drawn.Results A total of 26 patients needed the GIRD and were included in the final statistical analysis of the study. The procedure was done between 7th to 16th postoperative days (POD) and was successful in all patients without the need of any additional surgical procedure. None of the patients required any local anesthetic injection or any extra analgesics. The average time taken for procedure was 5-minutes and none of the patients had any significant difficulty in GI release. There were no immediate postprocedure complications.Conclusion The GIRD technique is a simple, safe, and quick procedure done around the 10th POD that can easily be performed by the bedside of patient without the need of any anesthesia or additional analgesics.
Keywords: ghost Ileostomy; ghost Ileostomy release down; low anterior resection; carcinoma rectum